A rare case of term viable abdominal pregnancy with review of literature - Agarwal, Manika; Sharma, Nalini; Jante, Vinayak; Panda, Subrat (Indian Journal of Case Reports, 2019)
Abdominal pregnancies are rare types of ectopic pregnancies with high rates of maternal and perinatal morbidity and mortality. Abdominal pregnancy accounts for up to 1.4% of ectopic pregnancies. We report a case of term live abdominal pregnancy without malformation with implantation of the placenta into the uterus and anterior abdominal wall, discovered during a planned obstetric hysterectomy indicated for placenta accreta. Abdominal pregnancy is a serious and potential life-threatening condition. Diagnosis and management can be difficult especially in developing countries. A high index of suspicion is key for timely diagnosis and intervention to prevent life-threatening complications.